2006
DOI: 10.1590/s0103-50532006000500022
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics of the interaction of pralidoxime and deazapralidoxime with acetylcholinesterase inhibited by the neurotoxic agent tabun

Abstract: Reativadores eficientes de Aceticolinesterase são fundamentais para o desenvolvimento de antídotos contra o envenenamento por pesticidas neurotóxicos e agentes de guerra química. Todavia, o mecanismo da reação de reativação e as características estruturais dos reativadores conhecidos são pouco compreendidos. Com o objetivo de estudar o comportamento dinâmico e o efeito da carga líquida do antídoto na reativação desta enzima, foi conduzido um estudo por dinâmica molecular da acetilcolinesterase humana inibida p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 24 publications
1
21
0
3
Order By: Relevance
“…10 The most effective reported reactivation compounds are cationic oximes prepared from pyridine aldehydes. As shown in Figure 3, 1,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] when they are converted to their conjugated bases, oximes are believed to function as nucleophiles. In this example, pralidoxime (2-PAM, 13) is converted to the anionic form (14), which makes a nucleophilic attack on the phosphate group, forming the phosphorylated oxime (15) and releasing the activity of AChE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 The most effective reported reactivation compounds are cationic oximes prepared from pyridine aldehydes. As shown in Figure 3, 1,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] when they are converted to their conjugated bases, oximes are believed to function as nucleophiles. In this example, pralidoxime (2-PAM, 13) is converted to the anionic form (14), which makes a nucleophilic attack on the phosphate group, forming the phosphorylated oxime (15) and releasing the activity of AChE.…”
Section: Introductionmentioning
confidence: 99%
“…51 In our previous work, the molecular dynamic simulation of the access of oximes to the active site of AChE inhibited with tabun confirmed that the cationic oxime 2-PAM reaches the active site easily, while its anionic form is rejected. 41 Clearly, the anionic form of 2-PAM is formed inside the AChE active site. In that work, it was also shown that a neutral oxime analogue to 2-PAM, deazapralidoxime or 2-methylphenylaldoxime (16) can effectively access the active site of AChE, indicating that neutral oximes could function as inhibitors of AChE or potential reactivators of AChE inhibited by organophosphorus compounds, with potential to act in the human brain.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Several molecular modelling studies available in literature point out to important features on the oximes structures that could be very useful to guide experimental research on this issue. [7][8][9][10][11][12][13][14][15][16][17][18][19] In a former work 4 …”
Section: Introductionmentioning
confidence: 99%
“…38,44,45 Moreover, the distribution of charged residues in AChE results in a permanent dipole moment that is aligned with the axis of the active site gorge; this characteristic facilitates the attraction of a positively charged substrate, guiding it through the gorge. 46 The direct interaction of the substrate with the negatively charged residues situated in the gorge is shielded by the side chains of the aromatic residues. 47 This electrostatic steering caused by the huge dipole moment, associated with the quadrupole and other multipole moments of the enzyme, contributes to its high catalytic efficiency.…”
Section: Ache Active Sitementioning
confidence: 99%